Reconstruction of Sharia Supervisor Frameworks in Islamic Banking: Strengthening to Enforcement Sharia Compliance - Hidayatullah, Muhammad Syarif; Azhari, Fathurrahman; Mahmud Yusuf; Muhammad, Aliyu Dahiru (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
As Islamic banking continues to expand beyond its traditional markets, the integrity of Sharia compliance emerges as a central concern within global financial governance. Nevertheless, much research revealed that Sharia supervision was still weak and not optimal. The research objective of this paper was to formulate a reconstruction of Sharia supervisors in Islamic banking as a solution to the Sharia supervision problem in Islamic banking, which was still considered weak and had not been optimal. This research was qualitative with a library research design. Based on the study conducted, the reconstruction of sharia supervisors as a solution to the problems of sharia supervision was carried out to overcome the problems of competence, independence, and effectiveness of supervisory performance. The reconstruction formulation was related to the certification of the Sharia Supervisory Board with the addition of training material on legislation and legal regulations for business and the financial industry, as well as strengthening the profession, the establishment of Sharia supervisory board regulations with provisions on the right to impose sanctions, then the decentralization of sharia supervisors with the formation of the Sharia Supervisory Secretariat of representative in the province with authority as regional coordinator.